IDENTIFIKASI DAN PERBAIKAN KERUSAKAN MESIN BUBUT HORIZONTAL GEMINIS NO. 19 MENGGUNAKAN METODE 5 WHY - Ariel, Ariel; Meidiantara , Muhammad Rizki; Ariyanto, Ariyanto; Napitupulu, Robert (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to identify the root cause of the failure of the No. 19 Horizontal Geminis Lathe at the Bangka Belitung State Polytechnic of Manufacturing and to recondition the machine to restore its functionality. The 5 Why method was used to analyze the electrical system failure, identifying that the damage to the manual circuit motor and diode was caused by a fragile and broken on/off lever due to lack of maintenance. After component replacement and repair, geometric testing showed that the machine met the established standards. The study concludes that the 5 Why method is effective in identifying root causes and that the repairs successfully restored machine performance. Recommendations are expected to improve the availability of lathes for student practicals and enhance understanding of systematic machine repair techniques.